Psychometric review of the perceived stress scale under CFA and Rasch models in Lima, Peru - Boluarte-Carbajal, Alicia (2023)
Stress is a public health disease that is increasing rapidly in the population worldwide, so it is necessary to take measures for detection and evaluation, through short scales. The purpose of the study was to analyze the psychometric properties of the Perceived Stress Scale (PSS) in a sample made up of 752 people with an age range of 18 to 62 years (M = 30.18, DE = 10.175), of whom 44% (331) were women and 56% (421) men, from Lima, Peru. The results, by means of confirmatory factor analysis and the Rasch model, confirmed the global adjustment of a 12-item (PSS-12) version with the presence of two orthogonal factors independent of each other, and also demonstrated the metric equivalence according to gender and adequate internal consistency. These results allow us to recommend the use of the PSS-12 in the Peruvian population for the measurement of stress.